Smart Grid communication applications: measurement equipment and networks architecture for data and energy flow - Tinton Dwi Atmaja; Dian Andriani; Rudi Darussalam (National Research and Innovation Agency, 2019)
Smart Grid is an advanced two way data and energy flow capable of self-healing, adaptive, resilient, and sustainable with prediction capability of possible fault. This article aimed to disclose Smart Grid communication in a logical way to facilitate the understanding of each component function. The study was focused on the improvement, advantages, common used design, and possible feature of Smart Grid communication components. The results of the study divide the Smart Grid communication application into two main category i.e. measurement equipment and network architecture. Measurement equipment consists of Advance Metering Infrastructure, Phasor Measurement Unit, Intelligent Electronic Devices, and Wide Area Measurement System. The network architecture is divided based on three hierarchies; local area network for 1 to 100 m with 100 kbps data rate, neighbour area network for 100 m to 10 km with 100 Mbps data rate, and wide area network for up to 100 km with 1 Gbps data rate. More information is provided regarding the routing protocol for each network from various available protocols. The final section presents the energy and data flow architecture for Smart Grid implementation based on the measurement equipment and the network suitability. This article is expected to provide a comprehensive guide and comparison surrounding the technologies supporting Smart Grid implementation especially on communication applications.